Holistic Integrative PIAUD Curriculum Meets Early Childhood Needs: Kurikulum PIAUD Holistik Integratif Memenuhi Kebutuhan Anak Usia Dini - Susilawati Maulid; Lina Revilla Malik; Kartika Fajriani (Indonesian Journal of Education Methods Development, 2026)
General Background Early childhood education requires a comprehensive curriculum that supports children’s cognitive, affective, psychomotor, moral, spiritual, health, nutritional, care, protection, and welfare needs. Specific Background In Islamic early childhood education, the PIAUD curriculum is expected to adapt to modern realities while maintaining Islamic values through child-centered and faith-based learning. Knowledge Gap However, the implementation of holistic integrative curriculum practices remains constrained by limited teacher competence, inadequate facilities, weak coordination, and the lack of practical examples for learning implementation. Aims This study aims to collect and analyze previous literature on the development of the holistic integrative PIAUD curriculum. Results The literature shows that holistic integrative PIAUD is necessary because early childhood learning requires comprehensive services involving education, health and nutrition, parenting, protection, and welfare. The findings also indicate that teachers, parents, communities, stakeholders, and academic actors have complementary roles in supporting curriculum implementation. Curriculum development can be carried out through guidebook preparation, expert validation, revision, and continuous evaluation. Novelty This study synthesizes recent literature to position holistic integrative PIAUD as a collaborative curriculum framework that connects Islamic values, child-centered learning, and multisector participation. Implications The findings provide a conceptual basis for strengthening curriculum planning, teacher readiness, institutional collaboration, and child-friendly Islamic early childhood education practices. Highlights• Comprehensive services include education, health, nutrition, care, protection, and welfare.• Teachers, parents, communities, and stakeholders share implementation responsibilities.• Guidebooks, expert validation, revision, and evaluation structure curriculum development. KeywordsPIAUD Curriculum; Holistic Integrative; Early Childhood; Islamic Education; Curriculum Development